Cognitive prehabilitation for older adults undergoing elective surgery: a systematic review and narrative synthesis - He, Yu; Wang, Ziliang; Zhao, Yinuo; Han, Xiaochai; Guo, Kangxiang; Sun, Nianyi; Liu, Xueyong (Frontiers in Aging Neuroscience, 2024)
Background Perioperative cognitive maintenance and protection in older adults is an important patient safety imperative. In addition to foundational care, one area of growing interest is integrating cognitive prehabilitation into the surgical trajectory. This review aimed to evaluate the effectiveness and safety of cognitive prehabilitation on cognitive functional capacity and postoperative cognitive outcomes among older adults undergoing elective surgery.The MEDLINE, Embase, CENTRAL, CINAHL, PsycINFO, PEDro, CBM, CNKI, WANFANG and VIP databases were systematically searched up to September 5, 2024, to identify randomized controlled trials published for English or Chinese. Two authors independently completed the study selection process, data extraction process and methodological quality assessment. The Patient, Intervention, Comparison, Outcome, Study design framework was used to construct the search strategy. The predefined primary outcomes of interest included the incidence of postoperative delirium (POD) and the incidence of delayed neurocognitive recovery (dNCR). The quality of the studies was evaluated by the PEDro scale. Owing to the small number of trials and clinical and methodological diversity, a narrative synthesis was undertaken in accordance with the Synthesis Without Meta-analysis guidelines. This study was conducted and reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses statement. The certainty of the evidence was assessed using the Grading of Recommendations Assessment, Development and Evaluation system.Results Six studies were analysed. These trials involved 645 total participants, with 316 in the intervention group (mean age, 66.0-73.8 years; 38.4%-77.8% male) and 329 in the comparator group (mean age, 67.5-72.6 years; 31.8%-88.9% male). The effects of preoperative cognitive training on reducing the incidence of dNCR, the incidence of POD, the length of hospital stay and the incidence of postsurgical complications as well as improving postoperative global cognitive function and activities of daily living are quite uncertain. The results of this study should be interpreted with caution owing to the limited number of trials and low to very low certainty of evidence.Conclusions Current evidence on the effectiveness and safety of cognitive prehabilitation on cognitive and noncognitive outcomes in older patients undergoing elective surgery is limited and unclear.